International Conference on Seakeeping and Weather, 28 February & 1 March, 1995, London - International Conference on Seakeeping and Weather (1995 : London, UK); The Royal Institution of Naval Architects (Great Britain); Nautical Institute (Great Britain) (London : Royal Institution of Naval Architects, 1995)
19